Effect of Y-doping on the phase relation and electrical properties of Fe-doped BaZrO3. Issue 2 (February 2018) - Kim, Dongyoung; Lee, Daae; Joo, Jong Hoon
Abstract: The effects of the co-doping of Y in Fe-doped BaZrO3 (BaZr0.7- y Fe0.3 Y y O3- δ ) on the phase relation and electrical properties are investigated in this study. While a single phase is formed up to y  = 0.1 by the substitution of Y for Zr-sites (phase-1), the amphoteric substitution of Y for both Zr-sites and Ba-site (phase-2) is observed above y  = 0.1. Electrical conductivity measurements suggest that p -type conduction prevails under an oxidizing atmosphere. The hole conductivity increases with an increase of Y concentration up to y  = 0.1, but a further increase of Y concentration causes a decrease in the conductivity. The maximum conductivities of both bulk and grain boundary are obtained at y  = 0.1, and a further increase of Y concentration leads to a decrease of the conductivity due to the possible formation of phase-2 with the partial replacement of Y for Ba-sites ( Y B a ). Partial proton conductivity is also improved by Y-doping up to y  = 0.1, but a further doping cannot contribute to an increase in the proton conductivity. The results indicate that the mixed proton and hole conductivity of Fe-doped BaZrO3 can be improved by the co-doping of a rare-earth acceptor (Y 3+ ), but the doping level is limited to y  = 0.1 to avoid the formation of phase-2.